If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x = 90 + -9x Solving 5x = 90 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 5x + 9x = 90 + -9x + 9x Combine like terms: 5x + 9x = 14x 14x = 90 + -9x + 9x Combine like terms: -9x + 9x = 0 14x = 90 + 0 14x = 90 Divide each side by '14'. x = 6.428571429 Simplifying x = 6.428571429
| (3)/(4+2i) | | 14x+16=6x-32 | | -2=8*0-2 | | -2x-3=3x-13 | | 2x+14=96 | | 17-(x+7)=6x-4 | | x+3(6-x)=6 | | log(x+1)-log(x-1)=1 | | 4(6y)=0 | | a^2-3ab+2a-6b= | | (m^4n)^-5/m^-2n^4 | | 2/3a=4 | | -10x+2=-8x+8 | | x^2+1=x^2+2nx+n^2 | | 0.875x+14=-2x+9 | | (x+2)(x-1)=70 | | y=0.875x+14 | | y=-3/5*0+3 | | y=-3/5*-0.6+3 | | 35+140x=875 | | 3.4*0-2.3y=-8.2 | | y=-4*0-36 | | p=n+k+mforn | | 4x+x=80 | | 5x-2(x-8)=4+4x | | 141-6x=4 | | 4*0+3.7y=-8.5 | | 6x+8=105-5x | | 3(x-1)-15= | | -6*8+8y=-48 | | -6*-6+8y=-48 | | y=(x+1) |